2013
DOI: 10.1016/j.stem.2013.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Genome-wide Approaches Identifies lncRNAs of Adult Neural Stem Cells and Their Progeny In Vivo

Abstract: SUMMARY Long noncoding RNAs (lncRNAs) have been described in cell lines and various whole tissues, but lncRNA analysis of development in vivo is limited. Here, we comprehensively analyze lncRNA expression for the adult mouse subventricular zone neural stem cell lineage. We utilize complementary genome-wide techniques including RNA-seq, RNA CaptureSeq, and ChIP-seq to associate specific lncRNAs with neural cell types, developmental processes, and human disease states. By integrating data from chromatin state ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
234
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(245 citation statements)
references
References 56 publications
7
234
0
2
Order By: Relevance
“…Importantly, these lncRNAs did not contain transcripts with coding potential, as measured by the two independent methods, including conservation-independent CPAT (22) and conservation-dependent PhyloCSF (23) (see Materials and Methods). About 85% of this data set overlapped previously identified lncRNAs (17,20,(34)(35)(36)(37)(38)) (see Fig. S1 in the supplemental material), supporting the accuracy of our prediction pipeline, with a total of 34% of all known lncRNAs recovered (Fig.…”
Section: Resultssupporting
confidence: 78%
“…Importantly, these lncRNAs did not contain transcripts with coding potential, as measured by the two independent methods, including conservation-independent CPAT (22) and conservation-dependent PhyloCSF (23) (see Materials and Methods). About 85% of this data set overlapped previously identified lncRNAs (17,20,(34)(35)(36)(37)(38)) (see Fig. S1 in the supplemental material), supporting the accuracy of our prediction pipeline, with a total of 34% of all known lncRNAs recovered (Fig.…”
Section: Resultssupporting
confidence: 78%
“…Given that lncRNAs are more tissue/cell-type specifically expressed and potentially regulated than protein-coding genes, 84,85 it is assume that they should have functions during the development of an organism, including the heart. Fendrr (Fetal-lethal noncoding developmental regulatory RNA) is 1 excellent example.…”
Section: Lncrnas In Cardiac Biology and Diseasesmentioning
confidence: 99%
“…Currently, the best characterized lncRNAs are typically polymerase II (Pol II) transcribed, multiexonic, 5' capped, alternatively spliced and polyadenylated. LncRNAs are usually expressed at a lower level than mRNAs but importantly are characterized by a greater tissue and cell specificity (4)(5)(6)(7). Recent studies have shown that lncRNAs regulate various biological processes such as chromosome inactivation (8), imprinting (9), splicing (10) and transcriptional control (11).…”
Section: Long Noncoding Rnas (Lncrnas)mentioning
confidence: 99%